Modern Trends in Administrative Local Self-Government Buildings Design in Cities - Osychenko, Halyna; Popova, Olha; Tyshkevych, Olga (International Journal of Engineering and Technology, 2018)
The article is aimed at trends identification in local self-government buildings design. Decentralization of authority processes require local self-government buildings design general strategy revision. The authors emphasize the necessity of new-type buildings design with architectural environment meeting authority openness and publicity needs. On the basis of the research methods chosen the authors provide an historical and comparative world analogues analysis for the objects researched and their design solutions, delineate historical typology of administrative buildings and identify peculiarities of modern City Halls design.The influence of modern authority democratization processes on administrative buildings architectural and design solutions have been highlighted in the article. The authors have identified modern trends in administrative buildings architectural design guided by a desire to transfer local self-government bodies into welfare services establishments and transform buildings into public spaces.Â